71.8k views
5 votes
.

(06.01)
Solve the following system of equations and show all work.

y=−x^2+6

y=3x−4

. (06.01) Solve the following system of equations and show all work. y=−x^2+6 y=3x-example-1
. (06.01) Solve the following system of equations and show all work. y=−x^2+6 y=3x-example-1
. (06.01) Solve the following system of equations and show all work. y=−x^2+6 y=3x-example-2
User Prakhar
by
6.1k points

1 Answer

2 votes
Since both equations equal y, you can set them equal to each other:
-x^2+6=3x-4
Move the x and 6 to the other side, since the x squared cannot stay negative and one side must equal 0.
0= x^2+3x-10, after this factor.
(x - 2 )(x + 5 )=0, solve each parenthese separately making it equal to 0.
x=2, -5

User Nanthakumar J J
by
6.0k points